2018
DOI: 10.1080/17470218.2016.1267233
|View full text |Cite
|
Sign up to set email alerts
|

Morphological structure influences the initial landing position in words during reading Finnish

Abstract: The preferred viewing location in words [Rayner, K. (1979). Eye guidance in reading: Fixation locations within words. Perception, 8, 21-30] during reading is near the word centre. Parafoveal word length information is utilized to guide the eyes toward it. A recent study by Yan and colleagues [Yan, M., Zhou, W., Shu, H., Yusupu, R., Miao, D., Krügel, A., & Kliegl, R. (2014). Eye movements guided by morphological structure: Evidence from the Uighur language. Cognition, 132, 181-215] demonstrated that the word's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 43 publications
4
40
1
Order By: Relevance
“…In two experiments, respectively implementing corpus-analytic and experimental control approaches, Yan et al (2014) reported consistent effects of morphological complexity on FL during the reading of Uighur script, an Arabic-derived agglutinative alphabetic language with rich suffixes. In a replication of their critical findings in Finnish, another morphologically rich language, Hyönä, Yan, and Vainio (2016) found that FL shifted closer to the word beginning for morphologically complex than for monomorphemic words. Lexical effects on fixation locations have also been reported for German (Hohenstein, Matuschek, & Kliegl, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…In two experiments, respectively implementing corpus-analytic and experimental control approaches, Yan et al (2014) reported consistent effects of morphological complexity on FL during the reading of Uighur script, an Arabic-derived agglutinative alphabetic language with rich suffixes. In a replication of their critical findings in Finnish, another morphologically rich language, Hyönä, Yan, and Vainio (2016) found that FL shifted closer to the word beginning for morphologically complex than for monomorphemic words. Lexical effects on fixation locations have also been reported for German (Hohenstein, Matuschek, & Kliegl, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…The two saccade-targeting hypotheses make opposite predictions: According to a strong version of the dynamic-adjustment hypothesis, target words that are high frequency or have clear boundaries should engender longer saccades because they are easier to process, while according to a strong version of the default-targeting hypothesis, such targets should increase the probability of the eyes being directed towards the centers of the targets because they are easier to segment. Of course, a hybrid account might predict that our manipulations differentially affect where the eyes move (e.g., see Hyönä, Yan, & Vainio, 2018)-a possibility that was also tested by the experiments reported next.…”
mentioning
confidence: 90%
“…The single fixation position is more likely to be at the beginning or middle of the word for Chinese and Japanese, and at the middle for alphabetic languages. In Uighur, an agglutinative language that relies on heavy use of suffixes, landing position is also influenced by the number of suffixes (M. Yan et al, 2014), suggesting that morphological structure of parafoveal words influences saccade programs (also found in Finnish; Hyönä, Yan, & Vainio, 2017).…”
Section: Other Eye Movement Corpora Based On the Psc Protocolmentioning
confidence: 99%